PROGRAM STUDI AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS 17 AGUSTUS 1945 SAMARINDA - Putri, Riska Diana (EKONOMIA, 2019)
The researchers really wanted to know the causes of errors and mistakes that often occur, including missing inventory items, as well as the purpose of this study, so that researchers know the internal control procedures contained in the trading company, so that the company gets additional insight into control procedures internally in accordance with the existing Internal Control Standards, as well as adding insight and references to the reader. The basic theory in this research is Accounting Information System, Accounting Information System is an information system that handles everything related to Accounting. The inventory accounting system aims to record the mutations of each type of inventory stored in the warehouse. Inventory security issues are the main problem experienced by every type of trading business. A good inventory internal control procedure is needed by trading companies because this is able to minimize these risks. based on the description, this study takes the title "Analysis of Internal Control of Merchandise Inventory at PT. Ramayana Lestari Sentosa Tbk. Samarinda Branch. Researchers this time also took the steps of qualitative methods that tend to use analysis and focus on facts in the field. The analytical tool used is a comparison of the relative values to determine the suitability of the company against the elements of internal control that are applied after conducting an interview by providing questions that have been provided in the form of questionnaires, so that researchers can find out the level of the procedures applied. The results of the study, it can be concluded that the procedures that exist at PT. Ramayana Lestari Sentosa Tbk. The Samarinda Branch is in full compliance with the existing Internal Control Standards, although there are still a few weaknesses, namely the vulnerability of theft in the sales area caused by a lack of equipment that can detect stolen items, damaged goods due to being too long in the warehouse.